Impact of longitudinal changes in serum uric acid levels and weight gain on new-onset atrial fibrillation—The Nishimura Health Survey: a retrospective cohort study - Satoaki Matoba; Satoshi Teramukai; Keitaro Senoo; Jun Munakata; Mitsuko Nakata; Muneaki Kumagai; Miyoko Yamaoka; Hiromi Nishimura (BMJ Open)
Objective Uric acid (UA) and obesity are significant risk factors for new-onset atrial fibrillation (AF). Based on the pathogenesis mechanisms of new-onset AF involving obesity and UA, it is possible that UA and weight gain may interact with each other. We investigated the impact of UA and weight gain on new-onset AF using a simple measure of weight change over time, ‘weight gain of ≥10 kg after age 20’.Design A retrospective cohort study.Setting and participants We retrospectively analysed 16 444 Japanese aged over 30 without AF from a cohort of employees undergoing annual health check-up from 2 April 2013 to 30 April 2022. We conducted a landmark survival analysis to assess the impact of longitudinal changes in UA and obesity on new-onset AF. Weight gain was defined as ‘weight gain of≥10 kg after age 20’ using a standardised self-administered questionnaire.Primary outcome measure Subjects were diagnosed with AF when AF was present in the electrocardiogram or when indicated in a patient interview.Result During a median follow-up period of 3.91 years, 69 new-onset AF occurred (incidence; 1.12/1000 person-years). UA levels were 5.76 (±1.37) in the weight gain group and 4.87 (±1.31) in the no weight gain group, both within normal limits. A multivariable landmark survival analysis including interaction term showed that new-onset AF was significantly associated with age, sex, baseline systolic blood pressure, baseline UA and the interaction term between UA change and weight gain. The interaction term between weight gain and UA change indicates that HR for every UA 1 mg/dL increase was 1.96 (95% CI 1.38 to 2.77) in subjects with weight gain and 0.95 (95% CI 0.61 to 1.48) in those without.Conclusion Even if UA levels are within the normal range, subsequent UA change and weight gain in adulthood have an interactive effect on new-onset AF.